2021
DOI: 10.1002/jhbp.1055
|View full text |Cite
|
Sign up to set email alerts
|

Single session endoscopic ultrasound‐guided double bypass (hepaticogastrostomy and gastrojejunostomy) for concomitant duodenal and biliary obstruction: A case series

Abstract: Background Concomitant malignant biliary and gastric outlet obstruction can be difficult to manage endoscopically with traditional endoscopic retrograde cholangiopancreatography (ERCP) and luminal stenting. Endoscopic ultrasound (EUS)‐guided hepaticogastrostomy (HG) and gastrojejunostomy (GJ) are novel techniques that can relieve both obstructions in a single session. This study aims to describe the outcomes of combined, single session EUS‐HG and EUS‐GJ. Methods This is a two‐center retrospective study of cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 47 publications
0
28
0
Order By: Relevance
“…EUS has revolutionized the endoscopic management of simultaneous biliary and GOO. However, limited non‐comparative series have mainly evaluated either individual procedures or single specific combinations in double obstruction 9–12 . Our study offers some insight on the risk of dysfunction of different combinations used in the management of double obstruction in three tertiary referral centers.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…EUS has revolutionized the endoscopic management of simultaneous biliary and GOO. However, limited non‐comparative series have mainly evaluated either individual procedures or single specific combinations in double obstruction 9–12 . Our study offers some insight on the risk of dysfunction of different combinations used in the management of double obstruction in three tertiary referral centers.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of AEs was 21% (no severe or fatal AE), whilst 13% required biliary re-interventions. 12 A recent meta-analysis suggested that EUS-CDS reduced the risk of reinterventions compared to EUS-HGS. 31 However, our findings suggest that choledochoduodenostomy drainage might be compromised in the context of a double obstruction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the endoscopist preferred HGS over CDS to decrease the risk of bleeding, stent misdeployment and potential making pancreatic surgical resection more difficult[ 67 , 97 ]. Of note, a study of 23 patients with concomitant duodenal and biliary obstruction undergoing single session EUS-HGS and gastrojejunostomy found that one patient with pancreatic cancer underwent successful pancreaticoduodenectomy 168 days post-biliary drainage and the fistula remained in situ with no complications[ 98 ]. On the other hand, in a large multicenter study comparing HGS ( n = 24 ) to CDS ( n = 23), the authors preferred CDS as it takes advantage of the anatomical proximity between the duodenal bulb and extrahepatic duct, by which puncture can be easier with shorter procedure times and less guidewire manipulation[ 85 ].…”
Section: Endoscopic Ultrasound Guided Biliary Drainagementioning
confidence: 99%